European health research and globalisation: is the public-private balance right? - McCarthy, Mark (BioMed Central, 2011)
BACKGROUND: The creation and exchange of knowledge between cultures has benefited world development for many years. The European Union now puts research and innovation at the front of its economic strategy. In the health field, biomedical research, which benefits the pharmaceutical and biotechnology industries, has been well supported, but much less emphasis has been given to public health and health systems research. A similar picture is emerging in European support for globalisation and health CASE STUDIES: Two case-studies illustrate the links of European support in global health research with industry and biomedicine. The European Commission's directorates for (respectively) Health, Development and Research held an international conference in Brussels in June 2010. Two of six thematic sessions related to research: one was solely concerned with drug development and the protection of intellectual property. Two European Union-supported health research projects in India show a similar trend. The Euro-India Research Centre was created to support India's participation in EU research programmes, but almost all of the health research projects have been in biotechnology. New INDIGO, a network led by the French national research agency CNRS, has chosen 'Biotechnology and Health' and funded projects only within three laboratory sciences. DISCUSSION: Research for commerce supports only one side of economic development. Innovative technologies can be social as well as physical, and be as likely to benefit society and the economy. Global health research agendas to meet the Millenium goals need to prioritise prevention and service delivery. Public interest can be voiced through civil society organisations, able to support social research and public-health interventions. Money for health research comes from public budgets, or indirectly through healthcare costs. European 'Science in Society' programme contrasts research for 'economy', using technical solutions, commercialisation and a passive consumer voice for civil society, compared with research valuing 'collectivity', organisational and social innovations, open use, and public accountability. CONCLUSIONS: European policy currently prioritises health research in support of industry. European institutions and national governments must also support research and innovation in health and social systems, and promote civil society participation, to meet the challenges of globalisation.